Body mass index and colorectal cancer risk: A Mendelian randomization study. Issue 4 (25th February 2021) - Suzuki, Shiori; Goto, Atsushi; Nakatochi, Masahiro; Narita, Akira; Yamaji, Taiki; Sawada, Norie; Katagiri, Ryoko; Iwagami, Masao; Hanyuda, Akiko; Hachiya, Tsuyoshi; Sutoh, Yoichi; Oze, Isao; et al.
Abstract: Traditional observational studies have reported a positive association between higher body mass index (BMI) and the risk of colorectal cancer (CRC). However, evidence from other approaches to pursue the causal relationship between BMI and CRC is sparse. A two‐sample Mendelian randomization (MR) study was undertaken using 68 single nucleotide polymorphisms (SNPs) from the Japanese genome‐wide association study (GWAS) and 654 SNPs from the GWAS catalogue for BMI as sets of instrumental variables. For the analysis of SNP‐BMI associations, we undertook a meta‐analysis with 36 303 participants in the Japanese Consortium of Genetic Epidemiology studies (J‐CGE), comprising normal populations. For the analysis of SNP‐CRC associations, we utilized 7636 CRC cases and 37 141 controls from five studies in Japan, and undertook a meta‐analysis. Mendelian randomization analysis of inverse‐variance weighted method indicated that a one‐unit (kg/m 2 ) increase in genetically predicted BMI was associated with an odds ratio of 1.13 (95% confidence interval, 1.06‐1.20; P value <.001) for CRC using the set of 68 SNPs, and an odds ratio of 1.07 (1.03‐1.11, 0.001) for CRC using the set of 654 SNPs. Sensitivity analyses robustly showed increased odds ratios for CRC for every one‐unit increase in genetically predicted BMI. Our MR analyses strongly support the evidence that higher BMI influences the risk of CRC. Although Asians are generally leaner than Europeans and North Americans, avoiding higher BMI seems to be important for the prevention of CRC in Asian populations. Abstract : Traditional observational studies reported a positive association between higher body mass index (BMI) and colorectal cancer (CRC) risk. However, these studies suffer from biases such as reverse causality and confounding. This Mendelian randomization study consistently showed that the genetically predicted higher BMI was associated with an increased risk of CRC in Japanese populations.